Contribution of metabolic reprogramming to genome instability in cancer progression - Woo, Ren He (2015)
Alterations in cellular metabolism in tumor cells have been shown to regulate histone acetylation that enriches the expression of genes associated with cell proliferation. This provided the basis to the present study where it attempts to address if Akt-induced metabolic reprogramming promotes aberrant cell proliferation, resulting in accelerating levels of DNA replication stress that consequently leads to the accumulation of DNA damages to the genome. The presence of DNA damage and the initiation of DNA damage responses were analyzed in (1) cells expressing a hyperactive form of Akt, (2) cells expressing a mutant form of Akt, and (3) cells with endogenous Akt reduced. Furthermore, to determine if Akt-induced histone acetylation regulates the expression of DNA damage response proteins, levels of BRCA1, Chk1 and p53 were determined in these cells. Results showed that Akt signaling induces elevated levels of γH2AX, a DNA damage marker, and phosphorylated of p53 at serine 15 and serine 20 that are associated with DNA damage responses. Also, the expression levels of p53 were increased in response to Akt signaling. These observations suggest that cell metabolism is a key mediator of epigenetic deregulation that promotes tumorigenesis and cancer progression, which require further analyses to confirm this.